2020
DOI: 10.3389/fonc.2020.01050
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Reduction of Spleen Density Is an Independent Predictor of Post-Operative Outcomes After Curative Gastrectomy in Gastric Cancer: A Multi-Center Study

Abstract: Objectives: The present study aimed to explore the association between spleen density and post-operative outcomes of patients after curative gastrectomy. Methods: From June 2014 to December 2015, we conducted a retrospective study to analyze pertinent clinical data from gastric cancer patients who underwent gastrectomy at the First and the Second Affiliated Hospital of Wenzhou Medical University. Spleen density was determined via computed tomography scans. Univariate and multivariate analyses were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The primary tumor of HCC patients can promote tumor progression and metastasis by inducing inflammation and regulating immunosuppression through the spleen (18,19). Wang et al demonstrated that the splenic radiomics model was an independent risk factor for the survival of patients with gastric cancer (17), and spleen density can predict the overall survival of patients with gastric cancer (31). All of the above suggests that the spleen has a close biological relationship with primary tumors' development.…”
Section: Discussionmentioning
confidence: 99%
“…The primary tumor of HCC patients can promote tumor progression and metastasis by inducing inflammation and regulating immunosuppression through the spleen (18,19). Wang et al demonstrated that the splenic radiomics model was an independent risk factor for the survival of patients with gastric cancer (17), and spleen density can predict the overall survival of patients with gastric cancer (31). All of the above suggests that the spleen has a close biological relationship with primary tumors' development.…”
Section: Discussionmentioning
confidence: 99%
“…Spleen density is a novel indicator of patient prognosis. It has been reported that DROSD is an excellent prognostic predictor in patients with gastric cancer and pancreatitis[ 12 , 13 ]. In our study, the incidence of DROSD was 32.9% in patients with ICC.…”
Section: Discussionmentioning
confidence: 99%
“…NLR is an indicator of immune system activity. Some studies have discussed that since NLR is higher in DROSD gastric patients, it could be an indicator of prognosis in gastric cancer patients[ 12 , 22 ]. Thus, NLR may be one of the factors affecting DROSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations